Health-related quality of life and expectations of patients before surgical treatment of lumbar stenosis - Pacola,Lílian Maria (2014)
OBJECTIVE: To evaluate the expectations of patients awaiting surgical treatment of lumbar canal stenosis and the association of Health-Related Quality of Life (HRQoL) with symptoms of anxiety and depression. METHODS: The sample included 49 patients from a university hospital. HRQoL was assessed by the Oswestry Disability Index (ODI) and 36-item Medical Outcomes Survey Short Form (SF-36) and symptoms of anxiety and depression by the Hospital Anxiety and Depression Scale (HADS). Expectations were investigated by means of questions used in international studies. Data were analyzed descriptively and by Student's t test. RESULTS: The mean time of disease progression was 34.5 months, the mean age was 58.8 years and 55.1% of the patients were women. Most patients had the expectation of improving with surgical treatment and 46.9% expected to be "much better" with regard to leg pain, walking ability, independence in activities and mental well being. The scores of anxiety and depression were respectively, 34.7% and 12.2%. We observed statistically significant differences between the groups with and without anxiety in the domains: General Health, Mental Health, and Vitality. Between the groups with and without depression there were statistically significant differences in the General Health and Mental Health domains. CONCLUSION: Patients showed great expectation to surgical treatment and the symptoms of anxiety and depression were related to some domains of HRQoL. Thus, the study contributes to broaden our knowledge and we can therefore guide the patients as to their expectations with respect to the real possibilities arising from surgery.